2010
DOI: 10.1161/atvbaha.109.200501
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the Ras–Extracellular Signal–Regulated Kinase 1/2 Pathway Is Involved in Smooth Muscle 22α–Mediated Suppression of Vascular Smooth Muscle Cell Proliferation and Neointima Hyperplasia

Abstract: Objective-Vascular smooth muscle cells (VSMCs) can switch between differentiated and dedifferentiated phenotypes, and this phenotype switch is believed to be essential for repair of vascular injury. We studied the inhibitory effect of smooth muscle 22␣ (SM22␣) on VSMC proliferation in vitro and in vivo and explored the potential molecular mechanisms of this effect. Methods and Results-By using coimmunoprecipitation and glutathione S-transferase pull-down assays, we have shown that SM22␣ binds to Ras in SM22␣-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 38 publications
2
64
1
Order By: Relevance
“…[16][17][18] Here, we further identified that the expression of SM22α at both the mRNA and protein level was decreased in VSMCs after PDGF-BB stimulation for 3 and 12 hours (Online Figure II; Figure 2C). Furthermore, we recently found that SM22α was polyubiquitinated after 6 hours of PDGF-BB stimulation.…”
Section: Sm22α K21 Ubiquitination Is Associated With Pdgf-bb-inducedmentioning
confidence: 60%
See 1 more Smart Citation
“…[16][17][18] Here, we further identified that the expression of SM22α at both the mRNA and protein level was decreased in VSMCs after PDGF-BB stimulation for 3 and 12 hours (Online Figure II; Figure 2C). Furthermore, we recently found that SM22α was polyubiquitinated after 6 hours of PDGF-BB stimulation.…”
Section: Sm22α K21 Ubiquitination Is Associated With Pdgf-bb-inducedmentioning
confidence: 60%
“…The increased numbers of BrdU-positive cells observed in the carotid arteries of SM22α −/− mice after ligation were decreased by reexpression of SM22α WT but not K21R mutant protein (Online Figure XF), although the PPP provides nucleotide precursors for cell proliferation, consistent with our previous findings. 16 Similarly, the percentage of TUNEL-stained cells also decreased under the same conditions ( Figure 6D). Furthermore, G6PD inhibition by 6-aminonicotinamide enhanced the inhibitory effect of SM22α on BrdU incorporation in carotid arteries from SM22α −/− mice after ligation ( Figure 6E; Online Figure XG and XH).…”
Section: Sm22α Ubiquitination Inhibits Apoptosis Via G6pd Activationmentioning
confidence: 62%
“…Such a regulation is responsible for the antiproliferative effect of the contractile phenotype marker SM22␣. SM22␣ binds Ras, resulting in downregulation of Ras-Raf-MAPK signaling and blockade of G 1 -S phase cycle progression in vascular smooth muscle cells (107). In vivo, this mechanism is responsible for SM22␣ overexpression-induced inhibition of neointimal hyperplasia induced by balloon injury (107).…”
Section: Ras Proteinsmentioning
confidence: 99%
“…SM22␣ binds Ras, resulting in downregulation of Ras-Raf-MAPK signaling and blockade of G 1 -S phase cycle progression in vascular smooth muscle cells (107). In vivo, this mechanism is responsible for SM22␣ overexpression-induced inhibition of neointimal hyperplasia induced by balloon injury (107). In the same way, R-Ras is a member of Ras protein family that antagonizes H-Ras signaling (88,438).…”
Section: Ras Proteinsmentioning
confidence: 99%
“…The protein expression for cyclinA, cyclinD1, cyclinE, CDK2, CDK4, CDK6, KLF4, p21, β-actin in HT-29 cells were examined by Western blot analysis as previously described (22). The blots were detected with the enhanced chemiluminescence detection system (Santa Cruz Biotechnology).…”
Section: Fluorescence Activated Cell Sorting (Facs) Analysismentioning
confidence: 99%